Keluhan Guru Mengenai Banyaknya Siswa Yang Tidur Di Kelas Saat Belajar Di PP Sumur Bandung - Euis Erni Sapriyani; Ageng Saepudin Kanda (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Learning activities must be paid attention to properly and correctly, therefore students must focus when learning begins. There are times when students are sleepy in class due to lack of sleep or staying up late at night. This research aims to find out how to help students not get sleepy and continue to learn well and stay focused in class. It is hoped that the results of this research can help teachers to deal with students who are sleepy during learning so that the material can be conveyed well. The research was conducted at PP Wells Bandung, Cililin District, West Bandung City. This research uses data collection techniques with qualitative methods, namely interviews, observation and documentation.